Pembangunan game “Recon Duty” dengan Godot Engine - Arkas Dyanta Ananda Kautsar; Tommy Bustomi; Muhammad Farman Andrijasa (JURNAL VOKASI TEKNIK, 2024)
The game "Recon Duty" is a shooting game with a camera angle from above looking down and also a Pixel Art visual display on every object, creature, and environment. This game is designed using the Godot engine with the GDScript language as a general programming language in the game engine application. Several stages of the Game Development Life Cycle (GDLC) consist of initiation, Pre-Production, Production, Evaluation, and Publication. The application of Artificial Intelligence (AI) to Non-Playable Characters (NPC) uses the pathfinding method to find a way to the target. The A-Star algorithm on NonPlayable Character (NPC) aims to determine the shortest path from the surrounding environment, so that it can reach the destination. This research produces a Recon Duty game that can be used as a means of entertainment for the community.